The Effectiveness of the Development of Discovery Learning Models to Improve Students' Mathematical Reasoning Skills - Harianti, Putri; Hutapea, Nahor Murani; Maimunah, Maimunah (Universitas Negeri Makassar, 2024)
The aim of the research is to see the effectiveness of developing a discovery learning model in improving students' mathematical reasoning abilities. The research population was all class VIII at SMPN 7 Rambah Samo. The research sample was classes VIII A and VIII B with 60 students. The data collection technique used is the test technique. The results of data processing were carried out with the help of the SPSS application. The normality test obtained sig. control class 0.200 and sig. experimental class 0.56. The control and experimental classes have sig. > 0.05 means that both classes have normal distribution. The homogeneity test obtained sig. 0.289 > 0.05 means that both classes have homogeneous variance. Next, an anova test was carried out with a significance level of 5%. The type of anova used is one way anova. The anova test results obtained sig. 0,000 < 5%. This means that there are differences in the effectiveness of developing discovery learning models to improve students' mathematical reasoning abilities. So, it can be concluded that the learning process using the discovery learning model is more effective in improving students' mathematical reasoning abilities than the learning process using a scientific approach.